Pariwisata Digital Populer: Kajian Destinasi Wisata Berbasis Video Game - Arditya Prayogi; Riki Nasrullah; Imam Prayogo Pujiono; Singgih Setiawan; Moh. Syaifuddin (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Digital tourism has grown rapidly with the advancement of information and communication technology, allowing tourists to explore destinations through digital media. One of the new trends in this field is the use of video games as a tool for tourism exploration and promotion. Some games, such as Assassin's Creed, present representations of real cities or fictional worlds that influence tourists' perceptions and encourage their interest in visiting related locations. However, there are still few studies that discuss in depth how experiences in video games can influence tourists' decisions in choosing tourist destinations. Therefore, this article aims to analyze the role of video games in shaping digital tourism trends and their impact on the tourism industry more broadly. This study uses a qualitative method with a literature review approach that includes an analysis of various literature related to digital tourism and the influence of video games on tourist destinations. Data sources consist of scientific journals, books, and research reports that are relevant to the topic. The results of the study show that video games can be an effective tourism marketing tool and provide an immersive virtual tourism experience through virtual reality (VR) and augmented reality (AR) technology. In addition to opening up new economic opportunities in the tourism sector, video games can also reduce the impact of overtourism by providing alternative digital tourism. However, there are challenges in the accuracy of cultural representation and technological accessibility. Therefore, collaboration between the tourism industry and game developers is needed to create inclusive, authentic and sustainable digital experiences.